Design of miniaturized multi-band hybrid-mode microstrip patch antenna for wireless communication - Yasameen Azeez; Maryam K. Abboud; Sara R. Qasim (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This research presents a small, compact microstrip patch antenna of multi-band antenna. The multi-band antenna can be scaled to higher frequencies, making it possibly useful in 5G applications. The antenna is made up of asymmetric scalene triangles slots on the right side of the patch, which is provided by the reference patch antenna. The modes of antenna, patch and slots are excited to obtain four bands. The antenna design is 25×25×1.4 mm3 resonant at 3.93 GHz, 4.25 GHz, 5.37 GHz, and 6.18 GHz. The simulated design shows a peak gain of 4.44 dB at 3.93 GHz, 5.63 dB at 4.25 GHz, 5.91 dB at 5.37 GHz and 5.2 dB at 6.18 GHz. The total efficiency at 3.93 GHz and 4.25 GHz is -1.152 dB and -0.5174 dB, at 5.37 GHz and 6.18 GHz shows a total efficiency of -0.535 dB and -0.566 dB. Finally, the antenna is fabricated and measured. A good agreement shown between measurements and fabrication in terms of return loss.